Sheikh Abdel Halim Mahmoud and his reform efforts at the Al-Azhar Al-Sharif Foundation (1964-1978 AD) (Journal of the College of Basic Education, 2022)
The folds of the study demonstrated the extent of the effectiveness of the social influences represented by the environment and religion in contributing to the crystallization and formation of the elite religious personality and making it in the character of permanence and continuity of the intellectual and religious giving in the Islamic reality and this was reflected on the personality of Sheikh Abdel Halim Mahmoud and his intellectual approach in the application of Islamic law through the formation of legal committees from Members of Al-Azhar Al-Sharif to write an Islamic constitution approved in the entire Islamic worldHe also identified the actual and applied indicators of his reformist ideas through his assumption of several administrative positions in Al-Azhar and the state through which he translated his path to achieve the desired goal of reforming Al-Azhar, expanding its scientific and administrative bodies and issuing reform laws, as well as paying attention to the floral scholarship for students of religious sciences and the opening of schools, centers and religious bodies. All over Egypt and the Islamic world, and restore Al-Azhar to its pioneering and supervisory role in the social life of the Muslim individual and rejecting religious violations, This made him a lot of confrontation with the Egyptian authority, headed by Anwar Sadat, which tried to encircle the role of Al-Azhar and impose power over it, especially in matters of legislating social laws that are inconsistent with Islamic law, and sometimes came to his resignation in protest against the authority's attempt to make Al-Azhar a mere state institution. He has a great role in framing the religious debate with the authorities on many religious and social issues